Unmanned fuel system using RFID tools - Usha, V; Saranya Jothi, C; Yuvaraj, G; M, Thanjaivadivel (International Journal of Engineering and Technology, 2018)
In current days, fuel stations are worked physically. These fuel pumps are tedious and require more labor. To put fuel stations in removed zone it expensive to give brilliant office to the purchasers all these issue are dealt with by the utilization of unmanned oil pump which requires less time to work and it is viable and can be introduced anyplace the client self-going to benefit the administrations the installment is finished by electron-ic clearing framework. The straightforward and legitimate utilization of microcontroller and GSM innovation gives an aggregate security and atomization in the conveyance of fuel. It has simple worked cell phone framework and client interface (GUI). It interfaces with rapid fuel gadget, which is advantageous for the purchaser to work. In our framework the watchword will be given to the client and client needs to enter this secret key on the LCD gave by the fuel station which will enable the oil to organization to make confirmation for the client additionally the dispersion of the fuel isn't conceivable until the point when it gets confirmed by the database. To put it plainly, we give a protected framework to fuel dissemination. The headway of this task can help industry monetarily.Â Â